Unveiling viral threats to temperate pome fruits: characterization, transmission, and sustainable management strategies - Manzoor, Subaya; Nabi, Sajad Un; Ayaz, Aadil; Rasool, Bushra; Sharma, Susheel K.; Chesti, M. H.; Parveen, Shugufta; Verma, M. K.; Diab, M. A.; Rabbee, Muhammad Fazle (Frontiers in Microbiology, 2025)
Apple (Malus × domestica Borkh.), pear (Pyrus communis L.), and quince (Cydonia oblonga Mill.) are widely cultivated fruit crops in temperate regions due to their desirable flavors and health benefits. However, their production is severely affected by various biotic stresses, with viral diseases being particularly significant challenge. These viral infections are of great economic importance, not only reduce tree vigor and yield but also compromise fruit quality and marketability. To date, more than 26 viruses and viroids have been identified as pathogens of these fruit trees. Many of these viral diseases persist as latent infections, causing permanent infections in these fruit trees. This review provides an overview of the viral pathogens affecting apple, pear, and quince, including their characterization, transmission modes, and the challenges they present for management. Emphasis is placed on accurate diagnosis and effective control strategies to mitigate the impact of these diseases in apple orchards.